2016
DOI: 10.1038/eye.2016.163
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric intraocular lens implants: accuracy of lens power calculations

Abstract: Purpose This study aims to evaluate the accuracy of lens prediction formulae on a paediatric population. Methods A retrospective case-note review was undertaken of patients under 8 years old who underwent cataract surgery with primary lens implantation in a regional referral centre for paediatric ophthalmology, excluding those whose procedure was secondary to trauma. Biometric and refractive data were analysed for 43 eyes, including prediction errors (PE). Statistical measures used included mean absolute error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…SE was more myopic in children who were treated using the SRK II formula than the SRK/T formula (SE −4.06 D vs −0.21 D, p < 0.001) at the last follow-up time. These results are in accordance with O’Gallagher et al [ 28 ]. It suggests that with the ELP calculation and the new formula, it is possible to perform an adequate predictive refraction in secondary IOL implantation in the ciliary sulcus of young children.…”
Section: Discussionsupporting
confidence: 93%
“…SE was more myopic in children who were treated using the SRK II formula than the SRK/T formula (SE −4.06 D vs −0.21 D, p < 0.001) at the last follow-up time. These results are in accordance with O’Gallagher et al [ 28 ]. It suggests that with the ELP calculation and the new formula, it is possible to perform an adequate predictive refraction in secondary IOL implantation in the ciliary sulcus of young children.…”
Section: Discussionsupporting
confidence: 93%
“…Eibschitz et al [ 20 ] conducted a spreadsheet program with AL (16 to 28 mm) and K (40 to 55 D) as input parameters to predict IOL power and reported that the Holladay 1 and Haigis formulas were highly accurate with similar performance in IOL prediction. O'Gallagher et al [ 21 ] enrolled 46 patients (67 eyes) undergone surgery younger than eight (mean 3.8 years) and analyzed the Hoffer Q, Holladay 1, SRK II, and SRK/T formulas prediction, and their results indicated that the SRK/T formula was the most accurate formula.…”
Section: Discussionmentioning
confidence: 99%
“…If the initial target is not achieved, then the outcome of future refraction in children becomes even more unpredictable. Previous studies have failed to establish a consensus on the formula that best predicts early postoperative refraction and these studies did not identify circumstances for each of these formulas that are highly relevant to the paediatric population.…”
Section: Introductionmentioning
confidence: 99%